Playing ‘for Real’: A Lab-Based Study of MMOGs - Jenson, Jen; Bergstrom, Kelly; de Castell, Suzanne (AoIR Selected Papers of Internet Research, 2013)
In this paper we report on a 3-year, mixed-methods study of Massively Multiplayer Online games, focusing on the ways in our lab-based studies were indeed sites of ‘real’ play, notwithstanding their limited ecological validity (Williams, 2010). We document the ways in which we observed players’ real commitment to a play session that had few or no opportunities for follow up – investing considerable time and attention to, for example, naming and customizing their avatars, and selectively equipping them. We illustrate here some of the insights available through lab-based play that cannot be captured otherwise. We also draw attention to the ways in which relying on only one type of data can create a false and/or incomplete picture of a participant’s level of engagement with the game. This research suggests that labs might well be a site where ‘authentic’ play is indeed possible, and can therefore offer rich potential for MMOG research as they can give significantly greater context than is possible from data that is generated by game servers.